Virtual Hybrids. From the Semiotics of Objects to the Semiotics of Collectives - Ventura Bordenca, Ilaria (E|C, 2023)
In this essay dedicated to a specific hybrid, the user VR headset, I will discuss how Semiotics, especially the Sociosemiotics of the last twenty years, has used the notion of hybrid and what are the specificities of its approach, especially the methodolog ical ones. Then specifically with regard to VR, I will deal with the formation of the user visual hybrid, taking into consideration what Latour says about the descriptive work of the ANT, which records the formation of hybrids where ruptures, crises, uncer tainties are created in the functioning of devices (and the use of a technical object for the first time falls among these). In order to do so I will refer to a brief ethnographic observation that involved a small group of first time users of visors and in particular I will highlight the somatic and pathemic aspect involved in the formation of the user visor hybrid, also referring to the First Steps tutorial (for Quest 2 visors). Finally, I will conclude with an evaluation of the design of certain visors an d the way they contribute to constructing the immersive experience, especially in the creation of the semantic relation between virtual world/real world